Salicylate induced exacerbation of ulcerative colitis. - Chakraborty, T K (1987)
The oral administration of mesalazine (5-aminosalicylic acid) resulted in the exacerbation of ulcerative colitis in two patients intolerant to sulphasalazine whose colitis had previously been quiescent. Although sulphasalazine intolerance is usually attributable to the sulphapyridine moiety, the possibility of salicylate sensitivity should be considered in colitic patients who fail to respond appropriately to sulphasalazine or who experience abdominal pain or diarrhoea while taking the drug.